The Influence Of Work Discipline And Work Facilities On Employee Productivity (Case Study Pt Mega Persada Indonesia – East Jakarta) - Rizal Rahmawan; Iwan Darmawansyah (Al-Makki Publisher, 2023)
Every company has a desire to be able to fulfill the interests of its members and shareholders. In this era, of course the company also has a goal to develop its business to be more advanced and have high competitiveness with other companies. To achieve these goals, the company must have qualified and superior human resources. The purpose of this research is to determine the effect of work facilities on employee productivity at PT Mega Persada Indonesia. Work discipline is a form of employee control to create behaviors that are consistent with company rules in the implementation of work that is more productive and shows the sincerity of work in the company. Work facilities are anything that can facilitate efforts and expedite work in order to achieve a goal. With the suspected hypothesis that there is an influence of work facilities on employee productivity at PT Mega Persada Indonesia. This research was conducted at PT Mega Persada Indonesia which is located at Jalan Raya Condet No.136 East Jakarta, DKI Jakarta 13250. The population is 75 employees. The sample is 75 people. Data analysis techniques include classical assumption tests, linearity tests, coefficient of determination analysis. Based on the results of data analysis and discussion, it was obtained that the calculated F value was 89.702 with a significance value of 0.000 (0.000 <0.05). Thus it can be concluded that work discipline and work facilities on employee work productivity. Based on the results of the coefficient of determination test (R2), it shows that work discipline work facilities and work training have an influence level of 0.714 (74.1%) on employee work productivity, while the rest 28.9% influenced by other factors. All X variables in this study (discipline and facilities) together have a positive and significant effect on employee work productivity.